THE ANNULMENT OF THE MARRIAGE CONTRACT FOR THE HATE - Shujauddin, Abdulmumen bin Abdulkader (Journal of Humanities & Social Sciences, 2018)
The Yemeni Personal Status Law differentiate in the text for the wife’s right in Annulment of her marriage contract If she was hated her husband. This text is Surmmarized and Mysterious that mixed between Annulment of the hatred and the Judicial separation and Annulment of the hurt. so this search study this topic and highlights it and presents appropriate conclusions and recommendations.